The Lions of Lucerne: Scot Harvath #1 - Thor, Brad; Copyright Paperback Collection (Library of Congress) (New York : Pocket Star Books, 2007)
In this incredibly fast-paced thriller, a conspiracy hatched close to the Oval Office results in the kidnapping of the president and the slaughter of a company of Secret Service agents commanded by ex-Navy SEAL Scot Harvath. The story careers from the ski slopes of Utah to the top of Switzerland's Mount Pilatus and sets Scot on an impossible mission: recover the president, evade renegade Swiss spy Gerhard Miner and his cadre of trained agents, and elude the American conspirators who are hot on his trail. Framed for murder, his reputation in tatters, his former colleagues turned against him, Harvath finds an unlikely ally in a beautiful Swiss prosecutor who's been checkmated by Miner once too often. Together they play a high-stakes game of mixed "doubles" to save the president and uncover the conspiracy.
Keywords: Intelligence officers -- Fiction; Americans -- Switzerland -- Fiction; Kidnapping -- Fiction; Presidents -- Fiction; Lucerne (Switzerland) -- Fiction; Suspense fiction